6a-9=6+9

Simple and best practice solution for 6a-9=6+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-9=6+9 equation:


Simplifying
6a + -9 = 6 + 9

Reorder the terms:
-9 + 6a = 6 + 9

Combine like terms: 6 + 9 = 15
-9 + 6a = 15

Solving
-9 + 6a = 15

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 6a = 15 + 9

Combine like terms: -9 + 9 = 0
0 + 6a = 15 + 9
6a = 15 + 9

Combine like terms: 15 + 9 = 24
6a = 24

Divide each side by '6'.
a = 4

Simplifying
a = 4

See similar equations:

| 8y-12-5y+8=0 | | -x^2-14x-33=0 | | 155-8a=19 | | -88=-8(1+2a) | | 12n+9=6-9 | | 12-8=n | | 108-4m^3=0 | | -5x+7(-4)=22 | | 5x+(-5x+6)=6 | | 4x+1=2x+c | | 7x+7=4x | | f(4)=19 | | 2x+18+12y= | | 10n-9=-199 | | -139+10f=831 | | 86x(34)100%= | | 10(18-x)=8(x+36) | | (2n-8n^2)+(5n^3+4n^2)= | | 12+x=13+y | | 2x-3=ab | | 2(x+5)+5(9-x)= | | 8y-5y+8=0 | | 2(3x-3)=-12+6x | | x+2/7-1=2 | | 4xy^2+3xy-(5yx+3x+x+2xy^2)=2xy^2-2xy-4x | | 2(3x-3)=-12+6 | | F(2)+f(4)= | | 4-(x+8)=-28 | | 5x-6=2x+8-14+3x | | 6x-16=4x-24 | | Y=-11x+12 | | f(x)=(tan^2*x)-(sin*4x) |

Equations solver categories